IMPLEMENTASI REWARD DAN PUNISHMENT DALAM PEMBELAJARAN DI MADRASAH SE-KOTA MEDAN - S Salminawati (Jurnal Al-Fatih, 2019)
This article discusses the implementation of reward and punishment in the teaching and learning system in Elementary Schools in Medan City. Rewardand punishment are two forms of external motivation that comes from the behavoristic theory. Reward and punishment are also two forms of teaching instruments to stimulate students' enthusiasm in learning activities. Reward is given to students who excel or students who have increased achievement while punishmentis given to students who have made mistakes or violations. The purpose of this research is to find out the implementation of reward and punishment in Elemantary Schools in Medan City. To achieve the above objectives, a qualitative approach is used in research. The results of the study shows that Islamic elementary schools in Medan have implemented these two methods, reward and punishment, but are still not optimal.